2015
DOI: 10.3390/metabo5010074
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomic and Environmental Variation of Metabolite Profiles in Marine Dinoflagellates of the Genus Symbiodinium

Abstract: Microorganisms in terrestrial and marine ecosystems are essential to environmental sustainability. In the marine environment, invertebrates often depend on metabolic cooperation with their endosymbionts. Coral reefs, one of the most important marine ecosystems, are based on the symbiosis between a broad diversity of dinoflagellates of the genus Symbiodinium and a wide phyletic diversity of hosts (i.e., cnidarian, molluscan, poriferan). This diversity is reflected in the ecology and physiology of the symbionts,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(54 citation statements)
references
References 100 publications
(122 reference statements)
2
51
1
Order By: Relevance
“…While our approach advances the field by providing a framework to investigate the roles of the symbiotic partners in a complex milieu, further metagenomic approaches will provide a detailed comparison between the functions of different microbes (Dinsdale et al ., ). Our findings lend weight to growing information on the metabolic role of mixed microbial communities, with various Symbiodinium types characterized by different chemical profiles (Klueter et al ., ) and shifts in associated bacterial/archaeal communities altering the metabolic potential of the holobiont (Wegley et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…While our approach advances the field by providing a framework to investigate the roles of the symbiotic partners in a complex milieu, further metagenomic approaches will provide a detailed comparison between the functions of different microbes (Dinsdale et al ., ). Our findings lend weight to growing information on the metabolic role of mixed microbial communities, with various Symbiodinium types characterized by different chemical profiles (Klueter et al ., ) and shifts in associated bacterial/archaeal communities altering the metabolic potential of the holobiont (Wegley et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…). These data also support a previous study with Symbiodinium in culture, which reported significant increases in pools of several inositol types (which were not identified) with elevated temperature in multiple Symbiodinium genotypes, suggesting that the accumulation of these groups may be a conserved response in Symbiodinium (Klueter et al ., ). Once again, the cellular roles of inositol derivatives and that of the wider signalling network within the cnidarian–dinoflagellate symbiosis warrant more in‐depth study; in particular, the potential roles of inositol in signal transduction in the holobiont during the breakdown of symbiosis (e.g.…”
Section: Discussionmentioning
confidence: 97%
“…) and their dinoflagellate symbionts (Klueter et al. ). This initial application was primarily concerned with methodology and reproducibility, but did identify differences in the metabolite profiles between coral species (Sogin et al.…”
Section: Discussionmentioning
confidence: 99%